DEVELOPMENT OF PROJECT BASED LEARNING ELECTRONICS MODULE ON INTERNET OF THINGS (IOT) MATERIAL WITH NODEMCU ESP32 - Sefiawati, Kiki; Nehru, Nehru; Amnie, Erlida (Jurnal PTK dan Pendidikan, 2024)
Based on observation sheets and interviews with Jambi University physics education students, it is known that there is no teaching material that can provide an overview to students about making Internet of Things (IoT) projects with NodeMCU ESP32 so that students still find it difficult in making Internet of Things (IoT) material projects with NodeMCU ESP32. This study aims to develop a project-based electronics module (Project Based Learning) on Internet of Things (IoT) material with NodeMCU ESP3. The method used is research (Research and Development) with the ADDIE model, including the analysis, design, and development stages. Module validation data is collected through a questionnaire sheet filled in by material validation and media validation. The results of material validation show that the module has a feasibility of 92% with a very feasible category, while the results of media validation show a feasibility of 90.16% with a very feasible category. Module trials were conducted on 27 Jambi University Physics Education students, which showed student perceptions of the module of 83.03% in the very good category. Based on these results, this module is considered feasible and effective as an alternative teaching material in learning electronics, especially on Internet of Things (IoT) material with NodeMCU ESP3 in university.